Biological indicators provide short term soil health assessment during sodic soil reclamation. (November 2015) - Dose, Heather L.; Fortuna, Ann-Marie; Cihacek, Larry J.; Norland, Jack; DeSutter, Thomas M.; Clay, David E.; Bell, Joel
Highlights: Producers need tools to determine impact of sodic soil remediation on soil health. Land use change from hayland to cropland reduced nitrification gene copy numbers. In sodium affected soils, gypsum application reduced soil enzyme activity levels. Successional vector trajectories help visualize soil health shifts due to management. Biological indicators are successful in measuring short term changes in soil health. Abstract: Sodic soil remediation is an expensive, lengthy process during which producers need tools to demonstrate that sodium (Na + ) remediation practices are improving soil health. The objective of this study was to determine if soil biological indicators can provide a short term assessment of the effectiveness of chemical management strategies used to remediate northern Great Plains sodium affected soils. This randomized complete block split-plot research experiment was conducted in a grassland which was converted to annual row crops. The soil at the site was an Exline (fine, smectitic, frigid Leptic Natrudolls). The experiment contained two drainage treatments (tile drained and no-drainage) and four chemical amendments (4.5 Mg ha −1 of gypsum, 9.1 Mg ha −1 of gypsum, 9.1 Mg ha −1 spent sugar beet lime, and a no amendment control). Base-line soil samples for biological assessment were collected in the fall of 2012 after tile drainage was installed. The sodium adsorption ratio (SAR) ranged from 0.4 to 16.7 with a range of electrical conductivity (EC) of 0.4–0.8 dS m −1 . Gypsum and lime amendments were applied in 2013. Soil samples were collected for assessing soil health before and after application of amendments and throughout the growing season. This study utilizes a novel application of successional vector trajectories to compare shifts in measured soil health parameters associated with land use change and remediation of sodicity. Soil samples were analyzed for percent total soil carbon (C), nitrifier and denitrifier gene copies, soil enzyme assays (nitrate reductase, ammonia monooxegenase, urease, β glucosidase, alkaline phosphatase, arylsulfatase and fluorescein diacetate hydrolysis), EC, pH, SAR, and soil texture. Gene copies and enzyme activities were successfully used to differentiate between land uses and amendment applications. Ammonia oxidizing bacterial gene copies were higher where cropland was amended with gypsum. Successional vectors verified a significant shift in soil health due to land use change and amendment application. Gypsum applications reduced SAR, but increased soil EC. This work demonstrates that soil enzyme activities and gene copy numbers can be used to detect improvements in soil health.